Impact of anxiety and depression disorders on adherence to anticoagulant therapy among patients with atrial fibrillation - R. S. Bogdanova; D. Yu. Shchekochikhin; A. Yu. Suvorov; B. A. Volel; A. V. Fomicheva; S. S. Belova; V. V. Ovsyannikova; D. G. Gognieva; F. Yu. Kopylov (Российский кардиологический журнал, 2022)
Aim. To determine the possible impact of anxiety and depression disorders on the adherence of patients with atrial fibrillation (AF) to anticoagulant the rapy.Material and methods. The study included outpatients with AF of any type. After signing the informed consent, patients filled out questionnaires and scales that determined the level of anxiety and personal predisposition (MMAS-8, MMAS-4, SF-36, SHAI, STAI, HADS, NEO-FFI).Results. A total of 117 outpatients treated for AF were included. The mean age of patients was 74±5 years (men, 38%). Based on MMAS-4 and MMAS-8 results, adherent and non-adherent cohorts of patients were formed. Low adherence group had significantly higher situational anxiety according to STAI (45,9±9,9 vs 41,1±10,7, p=0,045) and depression according to HADS (7,9±3,6 vs 5,9±3,5, p=0,018). SF 36 showed that non-adherent patients had a lower general health (41,6±12,9 vs 52,2±20,0, p=0,01). Five-factor model revealed an association between low compliance and low extraversion (21,3±6,6 vs 26,4±7,2, p=0,002). Pharmacokinetic data on blood concentrations of anticoagulants or its metabolites at the second visit were available in 76 (67%) patients. Assessment of pharmacokinetic and compliance data revealed a moderate direct correlation (Matthews correlation coefficient (MCC), 0,345) and a weak direct correlation with the MMAS-8 (MCC, 0,177). The difference in MMAS-4 and MMAS-8 scores between high and low pharmacokinetic adherence groups was significant on both scales (p=0,011 and 0,015, respectively).Conclusion. The rationale for widespread introduction of standardized questionnaires and scales (MMAS 4, MMAS 8, STAI, HADS, SF 36, Big 5) was shown in order to early identify patients with low adherence to treatment. The results highlight the need for further study of the contribution of psychiatric disorders to low compliance to anticoagulant therapy.